Modified Polyethersulfone (PES) Ultrafiltration Membranes for Enhanced Filtration of Whey Proteins - Cowan, Simone; Ritchie, Stephen (Separation science and technology, 2007)
Application of membrane technology to whey protein separation is an interesting development that has seen growth in recent years. In particular, modification of existing membranes to impart charge properties on the membrane surface or in the pores has been shown to improve membrane selectivity, product purity, and throughput of protein solutions. This paper focuses on exploring the effects of membrane charge and solution pH on filtration of the major whey proteins α-lactalbumin (14.1 kDa) and β-lactoglobulin (18.4 kDa) using functionalized PES membranes. The membranes have an open pore structure containing charged sulfonated grafted polymer chains that allows for greater protein retention. The modified membranes were synthesized by polymerization of styrene in the membrane pores followed by sulfuric acid treatment of the resulting polystyrene grafts. The charged membrane gave a calculated selectivity of five times better than the raw membrane at pH 7.2 based on data from single protein transmission experiments. The enhanced selectivity of the tailor-made membrane was due to increased retention of β-lactoglobulin due to a reduction in molecular sieving combined with electrostatic repulsion between negatively charged β-lactoglobulin and the negatively charged membrane.